PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN DAN KEBIJAKAN DEVIDEN TERHADAP NILAI PERUSAHAAN - Tanto, Tania Ivanna A.; Simanjuntak, Aaron M. A.; Pangayow, Bill J.C (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2020)
The value of the company is very important because the high value of the company will be followedÂ by the high prosperity of shareholders. The higher the stock price, the higher the value of theÂ company, in order to achieve company value, investors generally give their management toÂ professionals. Optimizing company value can be achieved through the implementation of financialÂ management functions, where one financial decision taken will influence other financial decisionsÂ and have an impact on the value of the company. This study aims to determine the effect of investmentÂ decisions, funding decision taken will influence other financial decision and have an impact on theÂ value of the company. This study aims to determine the effect of investment decisions, fundingÂ decisions and dividend policies on firm value. The population in this study are all companies listedÂ on the Indonesia Stock Exchange for the period 2014-2016 while sample selection using purposiveÂ sampling technique obtained 89 companies that will be used as samples in this study. The hypothesisÂ testing uses multiple regression analysis. The results of the study partially show that investmentÂ decision affect the value of the company, funding decisions do not affect the value of the companyÂ and dividend policy does not affect the value of the company. While the simultaneous research result shows that investment decisions, funding decisions and dividend policies have a significant effect onÂ firm value